Judicial politics and urban revolt in seventeenth-century France : the Parlement of Aix, 1629-1659 - Kettering, Sharon, 1942- (Princeton, New Jersey ; Surrey, England : Princeton University Press, 1978)
Most historical scholarship concerned with the Fronde has investigated the Parlement of Paris. By focusing on the different experience of high court judges in Aix-en-Provence, Sharon Kettering illuminates the causes of resistance to royal authority and offers a new understanding of the role of provincial officials in seventeenth-century revolts. The author shows that political tensions and alignments within the court and provincial capital were as important in causing the revolts at Aix as the judges' relationship with the crown. Describing the liaisons and personalities that gave impetus t.
Frontmatter -- CONTENTS -- LIST OF ILLUSTRATIONS -- LIST OF ABBREVIATIONS -- ACKNOWLEDGMENTS -- INTRODUCTION -- Chapter One. Provincial and Municipal Politics at Aix -- Chapter Two. The Estates and the Habsburg War -- Chapter Three. The Intendants of Justice and the Parlement -- Chapter Four. The Governors and the Parlement -- Chapter Five. The Cascaveoux Revolt of 1630 -- Chapter Six. The Opposition Party -- Chapter Seven. The Opposition Parlementaires -- Chapter Eight. The 1649 Revolt and the Fronde at Aix -- Chapter Nine. The Saint Valentine's Day Revolt of 1659 -- Conclusion -- Appendix I. Composition of the Aix Parlement, 1641-1649 -- Appendix II. Municipal Budget of Aix -- Appendix III. The Consuls and Assessors of Aix, 1629-1659 -- BIBLIOGRAPHY -- INDEX OF SUBJECTS -- INDEX OF NAMES -- Backmatter
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: France. -- Parlement (Aix-en-Provence); France. -- Parlement (Aix-en-Provence); Judges -- France -- Aix-en-Provence.; Aix-en-Provence (France) -- Politics and government; France -- Politics and government -- 17th century; France -- Politique et gouvernement -- 17e siècle.; HISTORY -- Europe -- France; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; Judges; Politics and government; France; France -- Aix-en-Provence; 1600-1699